CASE REPORT OCULAR MANIFESTATIONS IN A HIV POSITIVE AND SYPHILIS CO-INFECTION IN A 41 YEAR OLD MALE IN ALBANIA - Amarildo Belshi (European Scientific Journal, ESJ, 2015)
The incidence of HIV in Albania has increased over the last decade, particularly among men who have sex with men. The ocular involvement is a clinical manifestation of HIV. Syphilis is a sexual infection disease that in this increased in the last 10 years. A co-infection of HIV and syphilis appears to increase the risk of ocular manifestation. The ocular manifestation of the patients with a co infection HIV-Syphilis will present with unexplained visual complaint. I am presenting a case of an ocular syphilis in a patient HIV positive presented in the department of Ophthalmology in Mother Teresa Hospital.